2021
DOI: 10.3389/fneur.2021.600050
|View full text |Cite
|
Sign up to set email alerts
|

Voltage Gated Sodium Channel Genes in Epilepsy: Mutations, Functional Studies, and Treatment Dimensions

Abstract: Genetic epilepsy occurs as a result of mutations in either a single gene or an interplay of different genes. These mutations have been detected in ion channel and non-ion channel genes. A noteworthy class of ion channel genes are the voltage gated sodium channels (VGSCs) that play key roles in the depolarization phase of action potentials in neurons. Of huge significance are SCN1A, SCN1B, SCN2A, SCN3A, and SCN8A genes that are highly expressed in the brain. Genomic studies have revealed inherited and de novo m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 173 publications
(213 reference statements)
1
48
0
3
Order By: Relevance
“…SCN8A developmental and epileptic encephalopathy (SCN8A-DEE) is a rare and serious genetic epilepsy syndrome characterized by early-onset developmental delay and regression, cognitive impairment, and multiple intractable seizure types. [1][2][3] The SCN8A gene is highly expressed in the central nervous system and encodes the Nav1.6 voltage-gated sodium ion channel, which has a major role in regulating the excitatory neuronal networks in the brain. [1][2][3] The first human epileptogenetic SCN8A mutation to be identified was a missense gain-offunction mutation that altered the biophysical properties of the Nav1.6 sodium channel, as reported by Veeramah et al in 2012.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…SCN8A developmental and epileptic encephalopathy (SCN8A-DEE) is a rare and serious genetic epilepsy syndrome characterized by early-onset developmental delay and regression, cognitive impairment, and multiple intractable seizure types. [1][2][3] The SCN8A gene is highly expressed in the central nervous system and encodes the Nav1.6 voltage-gated sodium ion channel, which has a major role in regulating the excitatory neuronal networks in the brain. [1][2][3] The first human epileptogenetic SCN8A mutation to be identified was a missense gain-offunction mutation that altered the biophysical properties of the Nav1.6 sodium channel, as reported by Veeramah et al in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The SCN8A gene is highly expressed in the central nervous system and encodes the Nav1.6 voltage-gated sodium ion channel, which has a major role in regulating the excitatory neuronal networks in the brain. [1][2][3] The first human epileptogenetic SCN8A mutation to be identified was a missense gain-offunction mutation that altered the biophysical properties of the Nav1.6 sodium channel, as reported by Veeramah et al in 2012. [4][5][6] Subsequent studies have confirmed the critical role of SCN8A in the initiation and propagation of action potentials and neuronal activity in the brain, and almost 400 individuals with SCN8A-related epilepsy have been described in the literature or documented in registries.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations